Retoryka i metafizyka. Klasyczne podstawy nauczania papieskiego = Rhetoric and metaphysics. Classical roots of the Pope`s teaching - Heck, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Practical rhetoric by John Paul II is connected with metaphysics. "Inventio, disposito, elocutio" present in many of his texts result from his classical education. Thanks to these biographical factors, Karol Wojtyla was ready to cultivate the best of Latin, European and Polish tradition. In spite of conflicts between phenomenology and classical, realistic philosophy that were present in his epoch, the Pope succeed in gaining valuable knowledge from both idealism and, mainly, realism. Moreover, his ethical approach to rhetoric reminds that of the classics, Quintilian and Cicero.
Keywords: Jan Paweł II, papież (1929-2005); retoryka; metafizyka; nauczanie